Distribution of the neuro-regulatory peptide galanin in the human eye - Kaser-Eichberger, Alexandra; Trost, Andrea; Strohmaier, Clemens; Bogner, Barbara; Runge, Christian; Bruckner, Daniela; Hohberger, Bettina; Jünemann, Anselm; Kofler, Barbara; Reitsamer, Herbert A.; Schrödl, Falk (Neuropeptides, 2016)
Galanin (GAL) is a neuro-regulatory peptide involved in many physiological and pathophysiological processes. While data of GAL origin/distribution in the human eye are rather fragmentary and since recently the presence of GAL-receptors in the normal human eye has been reported, we here systematically search for sources of ocular GAL in the human eye. Human eyes (n=14) were prepared for single- and double-immunohistochemistry of GAL and neurofilaments (NF). Cross- and flat-mount sections were achieved; confocal laser-scanning microscopy was used for documentation. In the anterior eye, GAL-immunoreactivity (GAL-IR) was detected in basal layers of corneal epithelium, endothelium, and in nerve fibers and keratinocytes of the corneal stroma. In the conjunctiva, GAL-IR was seen throughout all epithelial cell layers. In the iris, sphincter and dilator muscle and endothelium of iris vessels displayed GAL-IR. It was also detected in stromal cells containing melanin granules, while these were absent in others. In the ciliary body, ciliary muscle and pigmented as well as non-pigmented ciliary epithelium displayed GAL-IR. In the retina, GAL-IR was detected in cells associated with the ganglion cell layer, and in endothelial cells of retinal blood vessels. In the choroid, nerve fibers of the choroidal stroma as well as fibers forming boutons and surrounding choroidal blood vessels displayed GAL-IR. Further, the majority of intrinsic choroidal neurons were GAL-positive, as revealed by co-localization-experiments with NF, while a minority displayed NF- or GAL-IR only. GAL-IR was also detected in choroidal melanocytes, as identified by the presence of intracellular melanin-granules, as well as in cells lacking melanin-granules, most likely representing macrophages. GAL-IR was detected in numerous cells and tissues throughout the anterior and posterior eye and might therefore be an important regulatory peptide for many aspects of ocular control. Upcoming studies in diseased tissue will help to clarify the role of GAL in ocular homeostasis.
EVALuna2:21283